Preweaned heifer management on US dairy operations: Part I. Descriptive characteristics of preweaned heifer raising practices - Urie, N.J. (J Dairy Sci, 2018)
The objective of this study was to describe preweaned dairy heifer calf management practices on dairy operations across the United States that were used to analyze factors associated with colostrum quality and passive transfer, Cryptosporidium and Giardia, morbidity and mortality, and average daily gain. This study included 104 dairy operations in 13 states that participated in the National Animal Health Monitoring System's Dairy 2014 calf component study. This 18-mo longitudinal study focused on dairy heifer calves from birth to weaning, and data were collected on 2,545 heifer calves. Descriptive statistics were generated regarding colostrum feeding, preweaning housing, milk feeding and consumption, growth, morbidity and mortality, and weaning practices. The majority of calves enrolled were Holsteins (89.4%). Over half the calves (63.2%) enrolled in the study received the majority of their colostrum via bottle; however, 22.1% of calves from 51.0% of operations received colostrum via suckling from their dams. For all calves, the mean time to the first colostrum feeding was 2.8 h, and the average amount of colostrum at the first feeding was 2.9 L, with 4.5 L provided in the first 24 h. The mean serum IgG of all calves was 21.7 g/L; however, 76.0% of operations had at least 1 calf with failure of passive transfer of immunity with a serum IgG below 10 g/L. The majority of calves in the study were housed individually (86.6%). Nonetheless, 20.2% of operations housed some calves in groups, representing 13.4% of all calves. Approximately one-half of the calves in the study (52.3%) were dehorned or disbudded during the preweaning period, with only 27.8% of these calves receiving analgesics or anesthetics during the procedure. Whole or waste milk was the liquid diet type fed to 40.1% of calves, and milk replacer was fed to 34.8% of calves. A combination of milk and milk replacer was fed to 25.1% of calves. Calves, on average, were fed 2.6 L per feeding and fed 2.6 times/d, resulting in a total of 5.6 L of liquid diet fed per day. The mean average daily gain for all calves enrolled in the study was 0.7 kg/d. Fecal samples were collected and almost all operations had at least 1 calf positive for Cryptosporidium (94.2%) or Giardia (99.0%), and 84.6% of operations had calves that tested positive for both Cryptosporidium and Giardia. Over one-third of calves (38.1%) had at least one morbidity event during the preweaning period and the mortality rate was 5.0%. The mean age at weaning was 65.7 d. This study provides an update on dairy heifer raising practices in the United States.